Response to Covid-19 Crisis: Recommendations and Health Policy Changes: Life Sciences-Virology - Aseel Bin Sawad; Fatema Turkistani (International Journal of Life Science and Pharma Research, 2022)
The World Health Organization (WHO) declared the pandemic status of coronavirus disease of 2019 (COVID-19). The necessity for social distancing has prompted states to make policy changes. These policy changes are in line with the policies and recommendations set by the WHO, the Centers for Disease and Control Prevention (CDC), the United States Department of Health and Human Services (HHS), the Centers for Medicare and Medical Services (CMS), the Kaiser Permanente, the National Institutes of Health (NIH), the United States Food and Drug Administration (FDA), and the American Medical Association (AMA). The aim of this study is to discuss and analyze the effectiveness of many organizations in responding to the COVID-19 crisis. Three processes were involved in conducting the narrative review: (1) a search was conducted through the websites of eight organizations (CDC, HHS, CMS, Kaiser Permanente, NIH, WHO, FDA, and AMA), (2) Selection of relevant information related to the responses taken by the eight organizations between January 21, 2020 and April 24, 2020 were included, (3) the information selected from the websites of the eight organizations were recorded, summarized, and integrated in this paper.COVID-19 is a health problem that needs to be approached in a collaborative manner. All eight organizations that have taken action against the further spread of the virus. The different policy changes and/or recommendations from the eight organizations have one common ground and that is the necessity for social distancing. To prevent overcrowding in hospitals and in other healthcare facilities, the organizations have decided to expand telehealth coverage. In Conclusions Health-related and policy-issuing organizations provided policies that are aligned with one another in order to contain the spread of COVID-19.